Pengaruh Budaya Organisasi, Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kinerja Karyawan PT. Jawa Pratama Mandiri - Chintya Septiana Safitri; Nurcholis Setiawan (Journal of Economic, Bussines and Accounting (COSTING), 2023)
This study aims to examine the influence of organizational culture, leadership style, work motivation, on employee performance. This research method uses quantitative methods. The data collection method used in this study uses a survey method using a questionnaire. Variables limited by organizational culture, leadership style support, work motivation and employee performance. In this study the population to be tested were all employees of PT Jawa Pratama Mandiri regarding the influence of organizational culture, leadership style and work motivation on employee performance. The samples studied were employees of PT Jawa Pratama Mandiri in production and administration who were permanent employees and had worked for at least 1 year. The sample in this study was 48 respondents. The results of this study prove that organizational culture has no significant direct effect on employee performance, leadership style has no significant effect on employee performance at PT Jawa Pratama Mandiri in Surabaya. Work motivation has a significant effect on employee performance at PT Jawa Pratama Mandiri in Surabaya. Keywords: Organizational Culture, Leadership Style, Work Motivation, Performance